Basalt fiber reinforced asphalt concrete material

By adding modifiers, modified polyurethane and basalt fibers to asphalt concrete to form asphalt concrete materials with semi-interpenetrating mesh structures, the problems of low mechanical strength and short service life of existing asphalt concrete are solved, and strength improvement and service life are achieved.

CN119707358APending Publication Date: 2025-03-28NINGBO DONGXING ASPHALT PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411927511.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

At this stage, the mechanical strength of asphalt concrete is not high and its service life is short.

Method used

The asphalt concrete material with a semi-interpenetrating mesh structure is formed by adding modifiers and modified polyurethane to the asphalt concrete and reinforced with basalt fibers.

Benefits of technology

It improves the mechanical strength and service life of asphalt concrete, and enhances the impact resistance and anti-ice effect of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005209572750000071
    Figure BDA0005209572750000071
  • Figure BDA0005209572750000081
    Figure BDA0005209572750000081
Patent Text Reader

Abstract

The invention discloses a basalt fiber reinforced asphalt concrete material, which is prepared from the following raw materials: matrix asphalt, a modifier, dicumyl peroxide, modified polyurethane, diethylenetriamine, modified basalt fiber, sandstone aggregate, mineral powder and benzoin diethyl ether. Under the action of benzoin diethyl ether, unsaturated double bonds in the modified polyurethane can be further grafted, then the strength of the asphalt concrete is enhanced, the internal crosslinking degree is increased, the modified polyurethane is matched with an organic silicon chain segment and a benzene ring structure in the modifier, the anti-freezing effect can be improved, diethylenetriamine can react with the modifier and the modified polyurethane, and the anti-freezing effect of the asphalt concrete is improved. According to the invention, a semi-interpenetrating grid structure can be formed, the surface of the modified basalt fiber is coated with the semi-interpenetrating grid structure to form a core-shell structure with a soft shell and a hard core, and when the material is impacted, the soft shell can generate plastic deformation, so that a large amount of energy is consumed, the impact can be counteracted, and the service life of the asphalt concrete material is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of asphalt concrete preparation, and in particular to a basalt fiber reinforced asphalt concrete material. Background Art

[0002] Asphalt concrete is a multiphase composite material formed by mixing asphalt, aggregates, fillers and other materials in a certain proportion. Asphalt concrete has good ductility and can better adapt to deformation caused by geological activities and building settlement. It is one of the main materials of modern road pavement structure and is widely used in various types of road pavements, especially suitable for high-speed road pavements. Asphalt concrete pavement has good mechanical properties and road performance, smooth pavement without joints, low vibration, comfortable driving, high traffic safety and other advantages. Therefore, it is favored by many designers and builders in highway construction. However, with long-term use, some road surfaces have been damaged, which increases the probability of traffic accidents. Summary of the invention

[0003] The purpose of the present invention is to provide a basalt fiber reinforced asphalt concrete material, which solves the problem of low mechanical strength and short service life of asphalt concrete at present.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] A basalt fiber reinforced asphalt concrete material specifically comprises the following steps:

[0006] Step A1: maleic anhydride and DMF are mixed evenly, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is added under stirring at a speed of 150-200 r / min and a temperature of 25-30° C., and the mixture is reacted for 1-1.5 hours. Acetic anhydride and sodium acetate are added, and the mixture is heated to 55-65° C. and reacted for 1-1.5 hours to obtain a modified end-capping agent. Tetramethyltetrasiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF are mixed evenly, and the mixture is reacted for 3-5 hours under a speed of 120-150 r / min and a temperature of 70-80° C. to obtain a modified monomer.

[0007] Step A2: octaphenylcyclotetrasiloxane, modified monomer, octamethylcyclotetrasiloxane, modified end-capping agent, tetramethylammonium hydroxide and DMF are uniformly mixed, and reacted for 2-3 hours at a speed of 150-200 r / min and a temperature of 105-110° C. to obtain a modifier, and basalt fiber is dispersed in ethanol, and KH550 and deionized water are added under stirring at a speed of 60-80 r / min and a temperature of 60-70° C., and reacted for 20-30 minutes to obtain modified basalt fiber;

[0008] Step A3: Add the base asphalt into the reactor, stir for 10-15 minutes at a speed of 1500-1600 r / min and a temperature of 130-140°C, then add the modifier and diisopropylbenzene peroxide, stir for 1-1.5 hours, add the modified polyurethane, stir for 10-15 minutes, add diethylenetriamine, modified basalt fiber, sand and gravel aggregate, mineral powder and benzoin ether, stir for 10-15 minutes, and obtain basalt fiber reinforced asphalt concrete material.

[0009] Further, the amount ratio of maleic anhydride, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, acetic anhydride and sodium acetate described in step A1 is 100mmo l:50mmo l:25mL:20mmo l, the molar ratio of tetramethyltetrasiloxane and allyl alcohol glycidyl ether is 1:4, and the amount of chloroplatinic acid is 1‰ of the mass of tetramethyltetrasiloxane.

[0010] Furthermore, the molar ratio of the octaphenylcyclotetrasiloxane, the modified monomer, the octamethylcyclotetrasiloxane, the modified end-capping agent and the tetramethylammonium hydroxide described in step A2 is 0.6:0.3:1.2:2:3, and the amount of KH550 used is 1% of the mass of the basalt fiber.

[0011] Furthermore, the weight ratio of the base asphalt, modifier, diisopropylbenzene peroxide, modified polyurethane, diethylenetriamine, modified basalt fiber, sand and gravel aggregate, mineral powder and benzoin ethyl ether described in step A3 is 6-7.5:2.5-3:1-1.2:1-1.2:2-2.4:0.1-0.3:100:10-12:0.1-0.2.

[0012] Further, the modified polyurethane is prepared by the following steps:

[0013] Step B1: Phenyltrimethoxysilane, isopropanol, sodium hydroxide and deionized water are mixed evenly, reacted for 3-5 hours at a speed of 120-150r / min and a temperature of 85-90°C, cooled to 20-25°C, reacted for 10-15 hours, and obtained octaphenyltetrasiloxane sodium tetrasiloxide; octaphenyltetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, stirred and methyldichlorosilane is added at a speed of 60-80r / min and a temperature of 0-3°C, reacted for 3-5 hours, heated to 20-25°C, and reacted for 20-24 hours to obtain dihydrogen cage-type silsesquioxane;

[0014] Step B2: Mix dihydrogen cage silsesquioxane, p-nitrostyrene, chloroplatinic acid and toluene, introduce nitrogen protection, react for 20-25 hours at a speed of 60-80 r / min and a temperature of 80-85° C. to obtain functionalized cage silsesquioxane; mix functionalized cage silsesquioxane, ferric chloride, aluminum chloride, activated carbon and DMF, stir and add hydrazine hydrate at a speed of 150-200 r / min and a temperature of 70-72° C., and react for 2-3 hours to obtain amino cage silsesquioxane;

[0015] Step B3: Mix polytetrahydrofuran ether diol, diphenylmethane diisocyanate, dibutyltin dilaurate and DMF evenly, introduce nitrogen protection, react for 2-3 hours at a speed of 60-80 r / min and a temperature of 75-80°C, add amino cage silsesquioxane, continue to react for 3-5 hours, add castor oil, and continue to react for 1-1.5 hours to obtain modified polyurethane.

[0016] Further, the amount ratio of phenyltrimethoxysilane, isopropanol, sodium hydroxide and deionized water described in step B1 is 6mmo l:6mL:4mmo l:7mmo l, and the amount ratio of sodium octaphenyltetrasiloxane tetrasiliconate, triethylamine, tetrahydrofuran and methyldichlorosilane is 12g:4.5g:30mL:3.5g.

[0017] Further, the molar ratio of the dihydrogen cage silsesquioxane and p-nitrostyrene described in step B2 is 1:2, the amount of chloroplatinic acid used is 1‰ of the mass of p-nitrostyrene, and the amount ratio of functionalized cage silsesquioxane, ferric chloride, aluminum chloride, activated carbon, DMF and hydrazine hydrate is 20mmo l:0.2g:0.2g:0.5g:50mL:3.5g.

[0018] Furthermore, the molar ratio of the polytetramethylene glycol, diphenylmethane diisocyanate, amino cage silsesquioxane and castor oil described in step B3 is 8:13:1:1, and the amount of dibutyltin dilaurate is 1% of the mass of diphenylmethane diisocyanate.

[0019] Beneficial effects of the present invention: A basalt fiber reinforced asphalt concrete material disclosed by the present invention is prepared by heating and stirring a base asphalt as a raw material, adding a modifier and diisopropylbenzene peroxide, grafting double bonds on the modifier with unsaturated double bonds in the base asphalt under the action of diisopropylbenzene peroxide, then adding modified polyurethane, grafting part of double bonds on the modified polyurethane with unsaturated double bonds in the base asphalt, then adding diethylenetriamine, which can react with the epoxy group in the modifier and the isocyanate in the modified polyurethane, and the modified basalt fiber can also be added to the reaction, and then adding sand and gravel aggregate, mineral powder and benzoin ethyl ether to obtain the asphalt concrete material.

[0020] The modifier uses maleic anhydride and 1,3-bis(3-aminopropyl)tetramethyldisiloxane as raw materials, and the maleic anhydride is ring-opened to react with the amino group on 1,3-bis(3-aminopropyl)tetramethyldisiloxane to obtain a modified end-capping agent. Tetramethyltetrasiloxane and acryl glycidyl ether are reacted to react the Si-H bond on tetramethyltetrasiloxane with the double bond on acryl glycidyl ether to obtain a modified monomer. Octaphenylcyclotetrasiloxane, the modified monomer and octamethylcyclotetrasiloxane are ring-opened and then polymerized with the modified end-capping agent to form a polysiloxane structure to obtain a modifier. The modified basalt fiber is treated with KH550 using basalt fiber as raw material to graft amino groups on the surface.

[0021] The modified polyurethane is prepared by hydrolyzing and condensing phenyltrimethoxysilane as a raw material to obtain sodium octaphenyltetrasiloxane tetrasilanolate, reacting sodium octaphenyltetrasiloxane tetrasilanolate with methyldichlorosilane so that the sodium silanolate on the sodium octaphenyltetrasiloxane tetrasilanolate reacts with the chlorine on the methyldichlorosilane to obtain dihydrogen cage silsesquioxane, reacting dihydrogen cage silsesquioxane with p-nitrostyrene so that the Si-H bond on the dihydro cage silsesquioxane reacts with the double bond on the p-nitrostyrene to obtain functionalized cage silsesquioxane, converting the nitro group of the functionalized cage silsesquioxane into amino group under the action of ferric chloride and aluminum chloride to obtain amino cage silsesquioxane, reacting polytetrahydrofuran ether diol with diphenylmethane diisocyanate, adding amino cage silsesquioxane for chain extension, and adding castor oil for hyperbranching to obtain the modified polyurethane.

[0022] During the use of asphalt concrete materials, ultraviolet rays are irradiated to the surface. Under the action of benzoin ethyl ether, the unsaturated double bonds in the modified polyurethane will be further grafted, thereby enhancing the strength of the asphalt concrete and increasing the internal cross-linking degree. Combined with the silicone segment and benzene ring structure in the modifier, it can increase the hydrophobicity of the asphalt concrete and thus increase the anti-icing effect. Diethylenetriamine can react with the modifier and modified polyurethane to form a semi-interpenetrating grid structure, and is coated on the surface of the modified basalt fiber to form a core-shell structure of a soft shell and a hard core. When the material is impacted, the soft shell can undergo plastic deformation, thereby consuming a large amount of energy, which can offset the impact and increase the service life of the asphalt concrete material. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Embodiment 1: A basalt fiber reinforced asphalt concrete material, comprising the following steps:

[0025] Step A1: maleic anhydride and DMF are mixed evenly, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is added under stirring at a speed of 150 r / min and a temperature of 25° C., and the mixture is reacted for 1 hour. Acetic anhydride and sodium acetate are added, and the mixture is heated to 55° C. and reacted for 1 hour to obtain a modified end-capping agent. Tetramethyltetrasiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF are mixed evenly, and the mixture is reacted at a speed of 120 r / min and a temperature of 70° C. for 3 hours to obtain a modified monomer.

[0026] Step A2: octaphenylcyclotetrasiloxane, modified monomer, octamethylcyclotetrasiloxane, modified end-capping agent, tetramethylammonium hydroxide and DMF are uniformly mixed, and reacted for 2 hours at a speed of 150 r / min and a temperature of 105° C. to obtain a modifier, and basalt fiber is dispersed in ethanol, and KH550 and deionized water are added under stirring at a speed of 60 r / min and a temperature of 60° C., and reacted for 20 minutes to obtain modified basalt fiber;

[0027] Step A3: Add the base asphalt into the reactor, stir for 10 minutes at a speed of 1500 r / min and a temperature of 130°C, then add the modifier and diisopropylbenzene peroxide, stir for 1 hour, add the modified polyurethane, stir for 10 minutes, then add diethylenetriamine, modified basalt fiber, sand and gravel aggregate, mineral powder and benzoin ethyl ether, stir for 10 minutes to obtain basalt fiber reinforced asphalt concrete material.

[0028] The amount ratio of maleic anhydride, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, acetic anhydride and sodium acetate described in step A1 is 100 mmol:50 mmol:25 mL:20 mmol, the molar ratio of tetramethyltetrasiloxane and allyl alcohol glycidyl ether is 1:4, and the amount of chloroplatinic acid is 1‰ of the mass of tetramethyltetrasiloxane.

[0029] The molar ratio of octaphenylcyclotetrasiloxane, modified monomer, octamethylcyclotetrasiloxane, modified end-capping agent and tetramethylammonium hydroxide described in step A2 is 0.6:0.3:1.2:2:3, and the amount of KH550 used is 1% of the mass of the basalt fiber.

[0030] The weight ratio of the base asphalt, modifier, diisopropylbenzene peroxide, modified polyurethane, diethylenetriamine, modified basalt fiber, sand and gravel aggregate, mineral powder and benzoin ethyl ether described in step A3 is 6:2.5:1:1:2:0.1:100:10:0.1, the base asphalt is 70 Grade A asphalt, the particle size of the sand and gravel aggregate is 2.36 mm, and the particle size of the mineral powder is 0.075 mm.

[0031] The modified polyurethane is prepared by the following steps:

[0032] Step B1: Phenyltrimethoxysilane, isopropanol, sodium hydroxide and deionized water are mixed evenly, reacted at a speed of 120 r / min and a temperature of 85° C. for 3 hours, then cooled to 20° C. and reacted for 10 hours to obtain sodium octaphenyltetrasiloxane tetrasiloxide; sodium octaphenyltetrasiloxane tetrasiloxide, triethylamine and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, stirred and methyldichlorosilane is added at a speed of 60 r / min and a temperature of 0° C., reacted for 3 hours, then heated to 20° C. and reacted for 20 hours to obtain dihydrogen cage-type silsesquioxane;

[0033] Step B2: Dihydrogen cage silsesquioxane, p-nitrostyrene, chloroplatinic acid and toluene are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 20 hours at a speed of 60 r / min and a temperature of 80° C. to obtain functionalized cage silsesquioxane; the functionalized cage silsesquioxane, ferric chloride, aluminum chloride, activated carbon and DMF are mixed evenly, and hydrazine hydrate is added at a speed of 150 r / min and a temperature of 70° C. to react for 2 hours to obtain amino cage silsesquioxane;

[0034] Step B3: Mix polytetrahydrofuran ether diol, diphenylmethane diisocyanate, dibutyltin dilaurate and DMF evenly, introduce nitrogen protection, react for 2 hours at a speed of 60 r / min and a temperature of 75°C, add amino cage silsesquioxane, continue to react for 3 hours, add castor oil, and continue to react for 1 hour to obtain modified polyurethane.

[0035] The amount ratio of phenyltrimethoxysilane, isopropanol, sodium hydroxide and deionized water described in step B1 is 6mmol:6mL:4mmo l:7mmo l, and the amount ratio of sodium octaphenyltetrasiloxane tetrasiliconate, triethylamine, tetrahydrofuran and methyldichlorosilane is 12g:4.5g:30mL:3.5g.

[0036] The molar ratio of the dihydrogen cage silsesquioxane and p-nitrostyrene described in step B2 is 1:2, the amount of chloroplatinic acid used is 1‰ of the mass of p-nitrostyrene, and the amount ratio of functionalized cage silsesquioxane, ferric chloride, aluminum chloride, activated carbon, DMF and hydrazine hydrate is 20mmo l:0.2g:0.2g:0.5g:50mL:3.5g.

[0037] The molar ratio of the polytetramethylene ether diol, diphenylmethane diisocyanate, amino cage silsesquioxane and castor oil in step B3 is 8:13:1:1, the amount of dibutyltin dilaurate is 1% of the mass of diphenylmethane diisocyanate, and the molecular weight of the polytetramethylene ether diol is 1000.

[0038] Embodiment 2: A basalt fiber reinforced asphalt concrete material, comprising the following steps:

[0039] Step A1: maleic anhydride and DMF are mixed evenly, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is added under stirring at a speed of 150 r / min and a temperature of 30° C., and the mixture is reacted for 1 hour. Acetic anhydride and sodium acetate are added, and the mixture is heated to 60° C. and reacted for 1.5 hours to obtain a modified end-capping agent. Tetramethyltetrasiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF are mixed evenly, and the mixture is reacted at a speed of 120 r / min and a temperature of 75° C. for 4 hours to obtain a modified monomer.

[0040] Step A2: octaphenylcyclotetrasiloxane, modified monomer, octamethylcyclotetrasiloxane, modified end-capping agent, tetramethylammonium hydroxide and DMF are uniformly mixed, and reacted for 2 hours at a speed of 150 r / min and a temperature of 110° C. to obtain a modifier, and basalt fiber is dispersed in ethanol, and KH550 and deionized water are added under stirring at a speed of 80 r / min and a temperature of 65° C., and reacted for 25 minutes to obtain modified basalt fiber;

[0041] Step A3: Add the base asphalt into the reactor, stir for 15 minutes at a speed of 1500 r / min and a temperature of 135°C, then add the modifier and diisopropylbenzene peroxide, stir for 1 hour, add the modified polyurethane, stir for 15 minutes, then add diethylenetriamine, modified basalt fiber, sand and gravel aggregate, mineral powder and benzoin ether, stir for 10 minutes to obtain basalt fiber reinforced asphalt concrete material.

[0042] The amount ratio of maleic anhydride, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, acetic anhydride and sodium acetate described in step A1 is 100 mmol:50 mmol:25 mL:20 mmol, the molar ratio of tetramethyltetrasiloxane and allyl alcohol glycidyl ether is 1:4, and the amount of chloroplatinic acid is 1‰ of the mass of tetramethyltetrasiloxane.

[0043] The molar ratio of octaphenylcyclotetrasiloxane, modified monomer, octamethylcyclotetrasiloxane, modified end-capping agent and tetramethylammonium hydroxide described in step A2 is 0.6:0.3:1.2:2:3, and the amount of KH550 used is 1% of the mass of the basalt fiber.

[0044] The weight ratio of the base asphalt, modifier, diisopropylbenzene peroxide, modified polyurethane, diethylenetriamine, modified basalt fiber, sand and gravel aggregate, mineral powder and benzoin ethyl ether described in step A3 is 7:2.8:1.1:1.1:2.2:0.2:100:11:0.2, the base asphalt is 70 Grade A asphalt, the particle size of the sand and gravel aggregate is 2.36 mm, and the particle size of the mineral powder is 0.075 mm.

[0045] The modified polyurethane is prepared by the following steps:

[0046] Step B1: Phenyltrimethoxysilane, isopropanol, sodium hydroxide and deionized water are mixed evenly, reacted at a speed of 120 r / min and a temperature of 90° C. for 4 hours, then cooled to 20° C. and reacted for 15 hours to obtain sodium octaphenyltetrasiloxane tetrasiloxide. Sodium octaphenyltetrasiloxane tetrasiloxide, triethylamine and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, stirred and methyldichlorosilane is added at a speed of 60 r / min and a temperature of 3° C., reacted for 4 hours, then heated to 20° C. and reacted for 24 hours to obtain dihydrogen cage-type silsesquioxane;

[0047] Step B2: Dihydrogen cage silsesquioxane, p-nitrostyrene, chloroplatinic acid and toluene are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 20 hours at a speed of 60 r / min and a temperature of 85° C. to obtain functionalized cage silsesquioxane; the functionalized cage silsesquioxane, ferric chloride, aluminum chloride, activated carbon and DMF are mixed uniformly, and hydrazine hydrate is added at a speed of 200 r / min and a temperature of 70° C. to react for 3 hours to obtain amino cage silsesquioxane;

[0048] Step B3: Mix polytetrahydrofuran ether diol, diphenylmethane diisocyanate, dibutyltin dilaurate and DMF evenly, introduce nitrogen protection, react for 2 hours at a speed of 60 r / min and a temperature of 80°C, add amino cage silsesquioxane, continue to react for 4 hours, add castor oil, and continue to react for 1.5 hours to obtain modified polyurethane.

[0049] The amount ratio of phenyltrimethoxysilane, isopropanol, sodium hydroxide and deionized water described in step B1 is 6mmol:6mL:4mmo l:7mmo l, and the amount ratio of sodium octaphenyltetrasiloxane tetrasiliconate, triethylamine, tetrahydrofuran and methyldichlorosilane is 12g:4.5g:30mL:3.5g.

[0050] The molar ratio of the dihydrogen cage silsesquioxane and p-nitrostyrene described in step B2 is 1:2, the amount of chloroplatinic acid used is 1‰ of the mass of p-nitrostyrene, and the amount ratio of functionalized cage silsesquioxane, ferric chloride, aluminum chloride, activated carbon, DMF and hydrazine hydrate is 20mmo l:0.2g:0.2g:0.5g:50mL:3.5g.

[0051] The molar ratio of the polytetramethylene ether diol, diphenylmethane diisocyanate, amino cage silsesquioxane and castor oil in step B3 is 8:13:1:1, the amount of dibutyltin dilaurate is 1% of the mass of diphenylmethane diisocyanate, and the molecular weight of the polytetramethylene ether diol is 1000.

[0052] Embodiment 3: A basalt fiber reinforced asphalt concrete material, comprising the following steps:

[0053] Step A1: maleic anhydride and DMF are mixed evenly, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is added under stirring at a speed of 200 r / min and a temperature of 30° C., and the mixture is reacted for 1.5 hours. Acetic anhydride and sodium acetate are added, and the mixture is heated to 65° C. and reacted for 1.5 hours to obtain a modified end-capping agent. Tetramethyltetrasiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF are mixed evenly, and the mixture is reacted at a speed of 150 r / min and a temperature of 80° C. for 5 hours to obtain a modified monomer.

[0054] Step A2: octaphenylcyclotetrasiloxane, modified monomer, octamethylcyclotetrasiloxane, modified end-capping agent, tetramethylammonium hydroxide and DMF are uniformly mixed, and reacted for 3 hours at a speed of 200 r / min and a temperature of 110° C. to obtain a modifier, and basalt fiber is dispersed in ethanol, and KH550 and deionized water are added under stirring at a speed of 80 r / min and a temperature of 70° C., and reacted for 30 minutes to obtain modified basalt fiber;

[0055] Step A3: Add the base asphalt into the reactor, stir for 15 minutes at a speed of 1600 r / min and a temperature of 140°C, then add the modifier and diisopropylbenzene peroxide, stir for 1.5 hours, add the modified polyurethane, stir for 15 minutes, add diethylenetriamine, modified basalt fiber, sand and gravel aggregate, mineral powder and benzoin ether, stir for 15 minutes, and obtain basalt fiber reinforced asphalt concrete material.

[0056] The amount ratio of maleic anhydride, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, acetic anhydride and sodium acetate described in step A1 is 100 mmol:50 mmol:25 mL:20 mmol, the molar ratio of tetramethyltetrasiloxane and allyl alcohol glycidyl ether is 1:4, and the amount of chloroplatinic acid is 1‰ of the mass of tetramethyltetrasiloxane.

[0057] The molar ratio of octaphenylcyclotetrasiloxane, modified monomer, octamethylcyclotetrasiloxane, modified end-capping agent and tetramethylammonium hydroxide described in step A2 is 0.6:0.3:1.2:2:3, and the amount of KH550 used is 1% of the mass of the basalt fiber.

[0058] The weight ratio of the base asphalt, modifier, diisopropylbenzene peroxide, modified polyurethane, diethylenetriamine, modified basalt fiber, sand and gravel aggregate, mineral powder and benzoin ethyl ether described in step A3 is 7.5:3:1.2:1.2:2.4:0.3:100:12:0.2, the base asphalt is 70 Grade A asphalt, the particle size of the sand and gravel aggregate is 2.36 mm, and the particle size of the mineral powder is 0.075 mm.

[0059] The modified polyurethane is prepared by the following steps:

[0060] Step B1: Phenyltrimethoxysilane, isopropanol, sodium hydroxide and deionized water are mixed evenly, reacted at a speed of 150 r / min and a temperature of 90° C. for 5 hours, then cooled to 25° C. and reacted for 15 hours to obtain sodium octaphenyltetrasiloxane tetrasiloxide. Sodium octaphenyltetrasiloxane tetrasiloxide, triethylamine and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, stirred and methyldichlorosilane is added at a speed of 80 r / min and a temperature of 3° C., reacted for 5 hours, then heated to 25° C. and reacted for 24 hours to obtain dihydrogen cage-type silsesquioxane;

[0061] Step B2: Dihydrogen cage silsesquioxane, p-nitrostyrene, chloroplatinic acid and toluene are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 25 hours at a speed of 80 r / min and a temperature of 85° C. to obtain functionalized cage silsesquioxane; the functionalized cage silsesquioxane, ferric chloride, aluminum chloride, activated carbon and DMF are mixed uniformly, and hydrazine hydrate is added at a speed of 200 r / min and a temperature of 72° C. to react for 3 hours to obtain amino cage silsesquioxane;

[0062] Step B3: Mix polytetrahydrofuran ether diol, diphenylmethane diisocyanate, dibutyltin dilaurate and DMF evenly, introduce nitrogen protection, react for 3 hours at a speed of 80 r / min and a temperature of 80°C, add amino cage silsesquioxane, continue to react for 5 hours, add castor oil, and continue to react for 1.5 hours to obtain modified polyurethane.

[0063] The amount ratio of phenyltrimethoxysilane, isopropanol, sodium hydroxide and deionized water described in step B1 is 6mmol:6mL:4mmo l:7mmo l, and the amount ratio of sodium octaphenyltetrasiloxane tetrasiliconate, triethylamine, tetrahydrofuran and methyldichlorosilane is 12g:4.5g:30mL:3.5g.

[0064] The molar ratio of the dihydrogen cage silsesquioxane and p-nitrostyrene described in step B2 is 1:2, the amount of chloroplatinic acid used is 1‰ of the mass of p-nitrostyrene, and the amount ratio of functionalized cage silsesquioxane, ferric chloride, aluminum chloride, activated carbon, DMF and hydrazine hydrate is 20mmo l:0.2g:0.2g:0.5g:50mL:3.5g.

[0065] The molar ratio of the polytetramethylene ether diol, diphenylmethane diisocyanate, amino cage silsesquioxane and castor oil in step B3 is 8:13:1:1, the amount of dibutyltin dilaurate is 1% of the mass of diphenylmethane diisocyanate, and the molecular weight of the polytetramethylene ether diol is 1000.

[0066] Comparative Example 1: Compared with Example 1, this comparative example uses basalt fiber instead of modified basalt fiber, and the other steps are the same.

[0067] Comparative Example 2: Compared with Example 1, no modifier was added in this comparative example, and the remaining steps were the same.

[0068] Comparative Example 3: Compared with Example 1, no modified polyurethane was added in this comparative example, and the remaining steps were the same.

[0069] Comparative Example 4: Compared with Example 1, amino cage silsesquioxane was not added in this comparative example, and the remaining steps were the same.

[0070] Comparative Example 5: Compared with Example 1, in this comparative example, the basalt fiber reinforced asphalt concrete material is irradiated with 365nm ultraviolet light for 1h, and the other steps are the same.

[0071] The asphalt concrete materials obtained in Examples 1-3 and Comparative Examples 1-5 were made into cylindrical specimens with a diameter of 100 mm and a height of 100 mm according to the standard of JTG-E20-2011, and the loading rate was 1 mm / min. The uniaxial compressive strength was tested. According to the standard of ASTM D638-03, specimens with a width of 20 mm, a length of 40 mm, and a thickness of 4 mm were made. The tensile strength was tested at a tensile rate of 500 mm / min. The test results are shown in Table 1 below.

[0072] Table 1

[0073]

[0074]

[0075] It can be seen from Table 1 above that the present application has good mechanical strength.

[0076] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A basalt fiber reinforced asphalt concrete material, characterized in that: The specific steps include: Step A1: maleic anhydride and DMF are mixed and stirred, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is added, and after reaction, acetic anhydride and sodium acetate are added, and the temperature is raised to react to obtain a modified end-capping agent, and tetramethyltetrasiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF are mixed and reacted to obtain a modified monomer; Step A2: octaphenylcyclotetrasiloxane, a modified monomer, octamethylcyclotetrasiloxane, a modified end-capping agent, tetramethylammonium hydroxide and DMF are mixed and reacted to obtain a modifier, basalt fibers are dispersed in ethanol, stirred and KH550 and deionized water are added, and reacted to obtain modified basalt fibers; Step A3: Add the base asphalt into the reactor, heat and stir, add the modifier and diisopropylbenzene peroxide, stir, add the modified polyurethane, stir, add diethylenetriamine, modified basalt fiber, sand and gravel aggregate, mineral powder and benzoin ethyl ether, stir, and prepare basalt fiber reinforced asphalt concrete material.

2. The basalt fiber reinforced asphalt concrete material according to claim 1, characterized in that: The amount ratio of maleic anhydride, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, acetic anhydride and sodium acetate in step A1 is 100mmol:50mmol:25mL:20mmol, and the molar ratio of tetramethyltetrasiloxane and allyl alcohol glycidyl ether is 1:

4.

3. The basalt fiber reinforced asphalt concrete material according to claim 1, characterized in that: The molar ratio of octaphenylcyclotetrasiloxane, modified monomer, octamethylcyclotetrasiloxane, modified end-capping agent and tetramethylammonium hydroxide described in step A2 is 0.6:0.3:1.2:2:3, and the amount of KH550 used is 1% of the mass of the basalt fiber.

4. The basalt fiber reinforced asphalt concrete material according to claim 1, characterized in that: The weight ratio of the base asphalt, modifier, diisopropylbenzene peroxide, modified polyurethane, diethylenetriamine, modified basalt fiber, sand and gravel aggregate, mineral powder and benzoin ethyl ether described in step A3 is 6-7.5:2.5-3:1-1.2:1-1.2:2-2.4:0.1-0.3:100:10-12:0.1-0.

2.

5. The basalt fiber reinforced asphalt concrete material according to claim 1, characterized in that: The modified polyurethane is prepared by the following steps: Step B1: Phenyltrimethoxysilane, isopropanol, sodium hydroxide and deionized water are mixed for reaction to obtain sodium octaphenyltetrasiloxane tetrasilanolate, sodium octaphenyltetrasiloxane tetrasilanolate, triethylamine and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, methyldichlorosilane is added after stirring, and a reaction is carried out to obtain dihydrogen cage-type silsesquioxane; Step B2: mixing dihydrogen cage silsesquioxane, p-nitrostyrene, chloroplatinic acid and toluene uniformly, introducing nitrogen protection, reacting to obtain functionalized cage silsesquioxane, mixing functionalized cage silsesquioxane, ferric chloride, aluminum chloride, activated carbon and DMF, stirring and adding hydrazine hydrate, reacting to obtain amino cage silsesquioxane; Step B3: uniformly mix polytetrahydrofuran ether diol, diphenylmethane diisocyanate, dibutyltin dilaurate and DMF, introduce nitrogen protection, react, add amino cage silsesquioxane, continue the reaction, add castor oil, continue the reaction, and obtain modified polyurethane.

6. The basalt fiber reinforced asphalt concrete material according to claim 5, characterized in that: The amount ratio of phenyltrimethoxysilane, isopropanol, sodium hydroxide and deionized water described in step B1 is 6mmol:6mL:4mmol:7mmol, and the amount ratio of sodium octaphenyltetrasiloxane tetrasiliconate, triethylamine, tetrahydrofuran and methyldichlorosilane is 12g:4.5g:30mL:3.5g.

7. The basalt fiber reinforced asphalt concrete material according to claim 5, characterized in that: The molar ratio of the dihydrogen cage silsesquioxane and p-nitrostyrene described in step B2 is 1:2, and the usage ratio of the functionalized cage silsesquioxane, ferric chloride, aluminum chloride, activated carbon, DMF and hydrazine hydrate is 20mmol:0.2g:0.2g:0.5g:50mL:3.5g.

8. The basalt fiber reinforced asphalt concrete material according to claim 5, characterized in that: The molar ratio of polytetramethylene ether diol, diphenylmethane diisocyanate, amino cage silsesquioxane and castor oil described in step B3 is 8:13:1:

1.

9. A basalt fiber reinforced asphalt concrete material, characterized in that: Prepared according to any one of the preparation methods described in claims 1-8.